Application of linear regression method to predict microcontroller-based infusion fluid volume using IoT - Adi Chandranata; Madona Era; Rinaldo Gamaliel Marbun (Jurnal Syntax Transformation, 2024)
Infusion is a medical device under certain conditions used to replay lost fluids and balance the body's electrolytes. In emergency condition for examples in patients with dehydration, severe metabolic stress that causes hypovolemic shock, acidosis, dengue hemorrhagic fever (DHF), burn hemorhagle shock and trauma,infusion are needed immediately to replace lost body fluids. The manufacture of this system use two LM393 Optocoupler Infrared Sensors. Infrared sensors detect deteeted objects, namely droplets. If no droples are detected, the infrared sensor will not work or is a cut-off condition. This system is the Internet of Things (IoT). With the platform used, Ubidots, so that monitoring can be done with a smartphone. A warning will be send the infusion level has reached 100ml, so Ubidots will automatically send a notification in the form of an E-mail.